Effect of H2O2 induced oxidative stress on volatile organic compounds in differentiated 3T3-L1 cells - Adebowale Samuel Oyerinde; Vaithinathan Selvaraju; Melissa Boersma; Jeganathan Ramesh Babu; Thangiah Geetha (Scientific Reports)
Abstract Oxidative stress (OS) refers to the disruption in the balance between free radical generation and antioxidant defenses, leading to potential tissue damage. Reactive oxygen species (ROS) can interact with biological components, triggering processes like protein oxidation, lipid peroxidation, or DNA damage, resulting in the generation of several volatile organic compounds (VOCs). Recently, VOCs provided new insight into cellular metabolism and can serve as potential biomarkers. The objective is to investigate the impact of OS on cell metabolism by analyzing the release or alterations of VOCs in the headspace of differentiated 3T3-L1 adipocytes. An OS model in differentiated 3T3-L1 cell lines was constructed using hydrogen peroxide (H2O2) treatment. The effect of OS on cell metabolism was analyzed by detecting VOCs in the headspace of the cells using solid phase micro extraction (SPME) and gas chromatography-mass spectrometry (GCMS). Our findings indicate that H2O2 concentrations exceeding 300 µM induce significant OS, leading to adipocyte apoptosis, as evidenced by various assays. Of the twenty VOCs identified, ten were upregulated in the cells. VOCs such as diphenyl ether, 1,3,5-trioxane, 5-methyl tridecane, 2-ethyl-1-hexanol, and 2,4-di-tert-butyl phenol emerged as potential biomarkers for OS. This study demonstrates that elevated OS alters VOC profiles in differentiated 3T3-L1 adipocytes, providing insights into the effects of OS on adipose tissue and identifying potential OS biomarkers.